Adenoviral vector‐based platforms for developing effective vaccines to combat respiratory viral infections. Issue 10 (12th October 2021) - Elkashif, Ahmed; Alhashimi, Marwa; Sayedahmed, Ekramy E; Sambhara, Suryaprakash; Mittal, Suresh K
Abstract: Since the development of the first vaccine against smallpox over two centuries ago, vaccination strategies have been at the forefront of significantly impacting the incidences of infectious diseases globally. However, the increase in the human population, deforestation and climate change, and the rise in worldwide travel have favored the emergence of new viruses with the potential to cause pandemics. The ongoing severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic is a cruel reminder of the impact of novel pathogens and the suboptimal capabilities of conventional vaccines. Therefore, there is an urgent need to develop new vaccine strategies that allow the production of billions of doses in a short duration and are broadly protective against emerging and re‐emerging infectious diseases. Extensive knowledge of the molecular biology and immunology of adenoviruses (Ad) has favored Ad vectors as platforms for vaccine design. The Ad‐based vaccine platform represents an attractive strategy as it induces robust humoral and cell‐mediated immune responses and can meet the global demand in a pandemic situation. This review describes the status of Ad vector‐based vaccines in preclinical and clinical studies for current and emerging respiratory viruses, particularly coronaviruses, influenza viruses and respiratory syncytial viruses. Abstract : This article describes the unique features of adenoviral (Ad) vector‐based vaccine platforms, activation of innate immunity leading to the development of balanced humoral and cell‐mediated immune responses, and potential drawbacks and their circumvention strategies. The progress of Ad vector‐based vaccines for coronaviruses, influenza viruses and respiratory syncytial viruses are discussed in detail.